The impact of Medicare Part D on opioid use among U.S. older adults. (1st July 2020) - Do, Duy
Highlights: Use of prescription opioids increased among US older adults in the past decades. Growing opioid use might be due to the expansion of Medicare Part D in 2006. There was no association between Part D and opioid use. Health insurance expansion is unlikely to have fueled the opioid epidemic. Abstract: Background: To assess the association between the implementation of Medicare Part D and the use of outpatient prescription opioids. Methods: Nationally representative data on community-dwelling adults aged 60–69 came from the 2000−2015 Medical Expenditure Panel Survey (MEPS) ( N = 26, 545). A difference-in-differences approach was used to compare opioid use between Medicare eligible (ages 66−69) and Medicare ineligible (ages 60−64) adults before and after the introduction of Part D in 2006, while controlling for socio-demographic characteristics, risk factors for opioid use, and secular trends. Results: Medicare Part D was associated with a small and statistically non-significant increase in the number of outpatient prescription opioids filled in a year (coefficient, 0.03; 95% CI, -0.08 to 0.13), in the amount of morphine milligrams equivalents (coefficient, 113.23; 95% CI, -25.47 to 251.93), and in the odds of using any prescription opioid (OR, 1.03; 95% CI, 0.85 to 1.26). There was no evidence for a heterogeneous effect of Part D across subgroups. The results were robust to the impacts of the 2007−2009 recession, the spillover effect of the Affordable Care Act, and the anticipation effect of Part D. Discussion: Although policymakers suggested that gaining access to medical care as a result of insurance expansion might have fueled the opioid epidemic, this paper found limited evidence to support this claim. While Part D took effect more than a decade ago, its long-term implication for opioid use is still relevant for the recent opioid epidemic and future health insurance expansions such as the proposed Medicare-for-all initiative.